(untitled) (Reflection and Critique Law Magazine, 2020)
This article focuses on issues related to discrimination and religious intolerance, focused on the work environment, as well as the challenges faced by both parties to ensure fairness to religion and belief in principles of article 5 of the Federal Constitution. Because religious freedom is a fundamental right and guarantee that must be guaranteed in any place, including at work. However, there are intense and numerous discriminatory practices for religious reasons. Therefore, the analysis is limited to demonstrating that the right of the employer to effect the dispensation finds limits in the principle of non-discrimination, which is one of the fundamental objectives of the Federative Republic of Brazil.